2013
DOI: 10.1098/rspb.2013.1224
|View full text |Cite
|
Sign up to set email alerts
|

Parallel changes in genital morphology delineate cryptic diversification of planktonic nudibranchs

Abstract: The relative roles of geographical and non-geographical barriers in the genesis of genetic isolation are highly debated in evolutionary biology, yet knowing how speciation occurs is essential to our understanding of biodiversity. In the open ocean, differentiating between the two is particularly difficult, because of the high levels of gene flow found in pelagic communities. Here, we use molecular phylogenetics to test the hypothesis that geography is the primary isolating mechanism in a clade of pelagic nudib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…; Churchill et al . ). However, a number of studies have found evidence for allopatric speciation in the plankton (Fleminger ; Darling et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Churchill et al . ). However, a number of studies have found evidence for allopatric speciation in the plankton (Fleminger ; Darling et al .…”
Section: Discussionmentioning
confidence: 97%
“…The addition of more slowly evolving unlinked markers should help resolve some poorly supported node at the base of the phylogenies presented here. Recently, Churchill et al [104] included the nuclear 28S gene in their phylogeny of Glaucidae. This provided a good resolution in deeper nodes, and therefore their 28S protocol will be included in further analyses as potentially useful in resolving within-aeolid relationships.…”
Section: Discussionmentioning
confidence: 99%
“…These species, originally recognized by molecular phylogenetics, were then corroborated by both internal and external morphological features (Hoover et al., ). Additionally, a phylogenetic analysis revealed two cryptic pairs in the aeolid nudibranch Glaucus marginatus (Churchill et al., ). However, in this instance, all four share the same external coloration, but each pair differs morphologically (presence or absence of the bursa copulatrix; Churchill et al., ).…”
Section: Introductionmentioning
confidence: 99%